Selective solid‐phase extraction of artificial chemicals from milk samples using multiple‐template surface molecularly imprinted polymers. (10th February 2015) - Zhang, Jing; Ni, Yan‐li; Wang, Ling‐ling; Ma, Jin‐qin; Zhang, Zhi‐qi
Abstract A novel multiple‐template surface molecularly imprinted polymer (MTMIP) was synthesized using ofloxacin and 17β‐estradiol as templates and modified monodispersed poly(glycidylmethacrylate‐co‐ethylene dimethacrylate) (PGMA/EDMA) beads as the support material. Static adsorption, solid‐phase extraction and high‐performance liquid chromatography were performed to investigate the adsorption properties and selective recognition characteristics of the polymer templates and their structural analogs. The maximum binding capacities of ofloxacin and 17β‐estradiol on the MTMIP were 9.0 and 6.6 mg/g, respectively. Compared with the corresponding nonimprinted polymer, the MTMIP exhibited a much higher adsorption performance and selectivity toward three quinolones and three estrogens, which are common drug residues in food. The MTMIP served as a simple and effective pretreatment method and could be successfully applied to the simultaneous analysis of multiple target components in complex samples. Furthermore, the MTMIP may find useful applications as a solid‐phase absorbent in the simultaneous determination of trace quinolones and estrogens in milk samples, as the recoveries were in the range 77.6–98.0%. Copyright © 2015 John Wiley & Sons, Ltd.